Use of a Research as Intervention Approach to Explore Telebehavioral Health Services During the COVID-19 Pandemic in Southeastern Idaho - Diana C. Schow; Ann Thomson; Wilson T. Trusty; Laurel Buchi-Fotre (SAGE Publishing, 2022)
Introduction: Since the inception of the COVID-19 pandemic, telebehavioral health services have been a key contributor to continuation of care in rural and underserved areas of southeastern Idaho. Providers of telebehavioral health services faced numerous challenges as they navigated rapidly shifting regulations, variable access to internet and their own personal understandings of practice. Objective: This study aimed to characterize provider experiences, generate policy- and practice-level recommendations, and raise awareness among community stakeholders regarding telebehavioral health in southeastern Idaho. Methods: Using a newly developed conceptual/analytical framework, a research-as-intervention strategy was employed to conduct and analyze semi-structured interviews, short writings, and photographs from 7 primary care and behavioral health providers in the region. Results: Providers shared examples from practice that addressed technology and training, access-to-care, safety, changing provider roles, payment for services, treatments that are not well suited to telehealth and the nuances of living and working in newly forged spaces of care. Conclusions: Providers found promise in telebehavioral health's utility as a hybrid model of care, but it must be supported by flexible legislation and policy. For example, it would help to make reimbursement expansions permanent and to simplify inter-jurisdictional practice options. Cross-sharing of information between licensing boards could help providers from various disciplines understand the parameters within which their colleagues must work.